Property Sales Data Processing Information System (SiPendar) - Suparni, Suparni; Utami, Lilyani Asri; Selviana, Elsa Dwi (Sinkron : jurnal dan penelitian teknik informatika, 2019)
PT. Pratama Mega Konstruksindo is one of the companies engaged in Property, especially Housing. One of the fields that requires technological progress is one of them is the property sector, the rapid development in the property sector is currently urging property service companies to meet the demands of the wider community. Implementation of work related to housing sales. In managing the data, this company still uses a manual system, starting from the recording and calculation aspects so that its performance has not been effective. At PT Pratama Mega Konstruksindo this still manages data using Ms Excel. As well as down payment, cash payments and consumer data are recorded using Ms Excel. This can cause errors in recording transactions, data security that is not guaranteed confidentiality, ineffective employees at work because it requires more time to input and make sales reports and even loss of data. Therefore, PT. Pratama Mega Konstruksindo requires a system that can solve the problem. This data processing system is designed web-based using the PHP and MySql programming languages as data storage databases. With the existence of this website, it can help processing sales data more effectively and efficiently, reports can be printed in realtime and data security can be maintained